PARENT COMMUNICATION PATTERNS AND RISK SEXUAL BEHAVIOR IN LATE ADOLESCENT - Cindy Wahyu Agustina; Sulistiawati, Sulistiawati; Setyoboedi , Bagus (UNIVERSITAS AIRLANGGA, 2024)
Background: Risky sexual behaviour in adolescents can have a detrimental impact on adolescent development and health, such as exposure to sexually transmitted diseases including HIV/AIDS, unwanted pregnancy, and abortion. Many factors can cause risky sexual behaviour, family factors, especially parental communication patterns are one of the most important influences, because parents are the environment that has the strongest preventive efforts in keeping adolescents involved in promiscuous activities. This study aims to find the relationship between parental communication patterns and risky sexual behaviour in late adolescents. Method: Observational analytic with cross-sectional research design. The sample size was 300 respondents with consecutive sampling technique. The independent variable is communication pattern. The dependent variable was risky sexual behaviour in late adolescents. The research data used instruments in the form of questionnaires and analysed using the Spearman's rank test with a significance level of p < 0.05. Result: Parental communication patterns in late adolescents were dominated by authoritative communication patterns at 56% and 63% of respondents have low-risk sexual behaviour. Spearman's rank test results p value < α, p = 0.000 and r = -0.239. Conclusion : Parental communication patterns have a relationship with risky sexual behaviour in late adolescents.